2016
DOI: 10.1016/j.ssc.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon heat exchange in layered nano-systems

Abstract: We analyze the heat power P between electrons and phonons in thin metallic films deposited on free-standing dielectric membranes in a temperature range in which the phonon gas has a quasi two-dimensional distribution. The quantization of the electrons wavenumbers in the direction perpendicular to the film surfaces lead to the formation of quasi two-dimensional electronic sub-bands. The electron-phonon coupling is treated in the deformation potential model and, if we denote by Te the electrons temperature and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 31 publications
(82 reference statements)
6
26
0
Order By: Relevance
“…At working temperatures, which are below 100 mK, the electron system in the normal metal is very weakly coupled to the phonons system. [25][26][27][28] This allows for the independent thermalization of the electrons system, at temperature T e , and of the phonons system, at temperature T ph . Then, the heat power between the electrons system and phonons system may be written in general aṡ…”
Section: Response Of the Cold Electron Bolometermentioning
confidence: 99%
See 1 more Smart Citation
“…At working temperatures, which are below 100 mK, the electron system in the normal metal is very weakly coupled to the phonons system. [25][26][27][28] This allows for the independent thermalization of the electrons system, at temperature T e , and of the phonons system, at temperature T ph . Then, the heat power between the electrons system and phonons system may be written in general aṡ…”
Section: Response Of the Cold Electron Bolometermentioning
confidence: 99%
“…We use the experimental values x = 5 and Σ ep = 4 × 10 9 Wm −3 K −513 instead of theoretical ones, calculated more recently, because the values existing in the literature (both, theoretical and experimental) vary significantly from model to model and from sample to sample (see the diversity of results presented, for example, in Refs. [13,[25][26][27][37][38][39][40][41][42][43]). For this reason we give priority to the measured parameters, in order to make more realistic calculations.…”
Section: Response Of the Cold Electron Bolometermentioning
confidence: 99%
“…The same is true for P (1) QWa /P (1) QW s . The sharp crests that appear parallel to the T e axis are exceptions to the simple power-law dependence of P 2D QW and are not discussed here (see [11] for details).…”
Section: Dmentioning
confidence: 99%
“…This interaction is described by the deformation potential Hamiltonian [10][11][12] where E F is the Fermi energy of the electrons, A is the area of the metallic film, d is the thickness (see Fig. 1), Ψ † (r) and Ψ(r) are the electron field creation and annihilation operators, respectively, whereas u is the phonon field.…”
mentioning
confidence: 99%
“…(1b), it was observed that s may take also fractional values: if the phonon gas is 2D and the electron gas distribution is a superposition of 2D conduction bands, then x = 3.5. 3,4 The exponent x depends on the effective dimensionality of the phonon gas, but the latter may change with temperature, as we discussed above. [5][6][7][8] Therefore, in a temperature range where the dimensionality of the phonon gas changes, the exponent x may also change,…”
Section: Introductionmentioning
confidence: 99%